New insights into mineralogy and geochemistry of allanite-bearing Mediterranean coastal sands from Northern Greece - Tzifas, I. T.; Papadopoulos, A.; Misaelides, P.; Godelitsas, A.; Goettlicher, J.; Tsikos, H.; Gamaletsos, P. N.; Luvizotto, G. [UNESP]; Karydas, A. G.; Petrelli, M.; Noli, F.; Kantarelou, V; et al. (Elsevier B.V., 2019)
Allanite-bearing black coastal sands of Kavala (N. Greece) were studied using a combination of single-crystal XRD, EMPA, mu-XRF, bulk ICP-MS, LA-ICP-MS, mu-XANES and gamma-ray spectrometry. The sands are rich in REE (Sigma REE + Y: 4010 to 10,810 mg/kg), Th (236-1205 mg/kg) and other critical metals such as Nb, Ta and Co. The main REE- and Th-hosts are allanite and titanite. The allanite unit cell parameters were calculated whereas its formula was found to be (REE0.470Ca1. 499Th0.031) (Ti0.031Fe1.089+3Al1.880) (Si-2.906Al0.094O12) (OH). The mu- XANES spectra showed that LREE are present in trivalent oxidation state. Analyses of the non-magnetic sand fractions showed higher LREE (12,470 mg/kg) due to accumulation of allanite. The materials showed elevated radioactivity ranging from 885 +/- 13 to 3467 +/- 20 Bq/kg. The obtained results provide new insights on the provenance of the sands, the abundance of REE, Th, and other immobile elements, and offer new clues for potential exploration and exploitation.
Keywords: Kavala; Beach placer; REE; Thorium; Allanite; mu-XRF; SR-XANES